Neuroprotective Effect of Hyperbaric Oxygen Therapy on Anterior Ischemic Optic Neuropathy - Avraham-Lubin, Bat-Chen R.; Dratviman-Storobinsky, Olga; Dadon-Bar El, Shimrit; Hasanreisoglu, Murat; Goldenberg-Cohen, Nitza (Frontiers in Neurology, 2011)
The study investigated the therapeutic effect of hyperbaric oxygen (HBO) on anterior ischemic optic neuropathy in a rodent model (rAION). rAION was laser-induced in one eye of 63 mice. The fellow (uninjured) eye served as an internal control. Thirty-three mice underwent two 90-minute sessions of 100% oxygen (2 Atm) treatment immediately following injury and one session daily thereafter for up to 14 days. The remaining mice were untreated. Retinas were harvested at different time points, and mRNA levels of various genes were analyzed by real-time polymerase chain reaction and histologic study. Untreated mice: day 1 post-rAION – SOD-1 (oxidative-stress-related) decreased to 82% of control (uninjured eye) levels (P<0.05), Caspase-3 (proapoptotic) decreased to 89%, Bcl-xL mildly increased (117%) (all NS); day 3 -- HO-1 and eNOS (ischaemia-related) decreased to 74%, and Bax, Caspase-3, and Bcl-2 (apoptotic) increased by 170%, 120%, and 111%, respectively (all NS); day 21 -- HO-1 increased to 222% (NS) and eNOS decreased to 48% (P<0.05). Treated mice: day 1 -- SOD-1 and Caspase-3 remained unchanged, Bcl-2 and Bcl-xL mildly increased (112% and 126% respectively); day 3 --.HO-1 and eNOS increased, apoptosis-related gene decreased; day 21 -- SOD-1 decreased whereas eNOS increased (P<0.05), and HO-1 increased to a lesser degree than without treatment. None of the oxygen-treated animals had retinal ganglion cell loss or a decrease in Thy-1 expression. In conclusion, HBO treatment after rAION induction influences the expression of apoptosis-related genes as well as oxidative-stress-induced and ischaemia-related genes and may exert a neuroprotective effect.